Dark catalysis. Issue 8 (17th August 2017) - Agrawal, Prateek; Cyr-Racine, Francis-Yan; Randall, Lisa; Scholtz, Jakub
Abstract: Recently it was shown that dark matter with mass of order the weak scale can be charged under a new long-range force, decoupled from the Standard Model, with only weak constraints from early Universe cosmology. Here we consider the implications of an additional charged particleC C that is light enough to lead to significant dissipative dynamics on galactic times scales. We highlight several novel features of this model, which can be relevant even when theC C particle constitutes only a small fraction of the number density (and energy density). We assume a small asymmetric abundance of theC C particle whose charge is compensated by a heavyX X particle so that the relic abundance of dark matter consists mostly of symmetricX X and\bar{X} X̄, with a small asymmetric component made up ofX X andC C . As the universe cools, it undergoes asymmetric recombination binding the freeC C s into(XC) ( XC ) dark atoms efficiently. Even with a tiny asymmetric component, the presence ofC C particles catalyzes tight coupling between the heavy dark matterX X and the dark photon plasma that can lead to a significant suppression of the matter power spectrum on small scales and lead to some of the strongest bounds on such dark matter theories. We find a viable parameter space where structure formation constraints are satisfied and significant dissipative dynamics can occur in galactic haloes but show a large region is excluded. Our model shows that subdominant components in the dark sector can dramatically affect structure formation.